2006
DOI: 10.1007/bf03022837
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Organ per fusion/permeabilityrelated effects of norepinephrine and vasopressin in sepsis

Abstract: Purpose:One invariable hallmark of severe sepsis is generalized tissue "malperfusion" and hyperpermeability secondary to microcirculatory/capillary leakage. This review focuses on direct and/or indirect influences of norepinephrine, as a standard of care, and vasopressin, as an alternative vasoactive drug, on organ and tissue perfusion/permeability in severe sepsis.Source: English and French language articles and books published between 1966 and 2005 were identified through a computerized Medline search using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 101 publications
1
19
0
1
Order By: Relevance
“…Besides excessive vasodilation and cardiac depression, severe endothelial dysfunction represents another hallmark of sepsis, resulting in microvascular hyperpermeability and transvascular flux of fluids and proteins [28]. This condition is typically associated with significant formation of edema and may even be a contributor to increased mortality in critically ill patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…Besides excessive vasodilation and cardiac depression, severe endothelial dysfunction represents another hallmark of sepsis, resulting in microvascular hyperpermeability and transvascular flux of fluids and proteins [28]. This condition is typically associated with significant formation of edema and may even be a contributor to increased mortality in critically ill patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…But with increasing dosage or prolonged duration, side effects like increased heart rate and increased myocardial oxygen consumption occur. The elevation of systemic vascular resistance can also compromise end organ perfusion [2,3]. In addition refractoriness to catecholamines exists [4].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, because splanchnic blood flow, being a non-critical organ bed, is not protected, gastrointestinal blood flow has been reported to be susceptible to AVP (90,91), although this was not confirmed in two prospective controlled studies (3,59), and bowel necrosis was rarely reported. Dose-independent coronary spasms or vasoconstriction inducing diastolic heart dysfunction, as well as dose-dependent negative inotropic effects, have occasionally been observed with AVP infusion (37,51,59,92,93). Increases in liver enzymes and bilirubin concentrations during sepsis and post-CBG shock can also occur with AVP administration (84).…”
Section: Exogenous Avp Redistributive Shock and Critical Illness-relmentioning
confidence: 91%